Correction system for polyphonic piano recordings - Martin Erdozain, Maria Isabel; Barbancho-Pérez, Isabel; Rosa-Pujazon, Alejandro; Barbancho-Pérez, Ana María (My University, 2013)
n this paper, a support tool for piano rehearsal is presented. The system analyses a given piano polyphonic recording to find the times, pitch and duration of the notes and figures played, taking into account the possibility of playing more than one note simultaneously as well as covering the whole piano frequency range. In order to do so, the system uses an onset detection algorithm to segment the input signal into partitions which are then analysed in the time and frequency domains. Then, the system correlates the data extracted from the partitions with the score of the original piece, identifying the positions and type of the mistakes performed by the user, and providing her/him with the corresponding feedback. The experiments conducted showed that the application is capable of analysing a given recording and indicate the musician the mistakes made.
M.I. Martin-Erdozain, I. Barbancho, A. Rosa-Pujazon, A.M. Barbancho, "Correction system for polyphonic piano recordings", XXVIII Simposium Nacional de la Unión Científica Internacional de Radio, Santiago de Compostela, España, 2013
Keywords: Piano; Polifonía; polyphonic, piano, transcription